Prince Prances Again - Grovet, Heather; Nang Chan Yeema (Nampa, ID USA Pacific Press Publishing Association, 2001)
Janelle is happy to finally have a pony of her own, but when her new friend Katie almost ruins her summer, Janelle must pray hard to Jesus before she can forgive Katie.
Keywords: Adult Fiction